The Relationship between the Injury Mechanism and the Incidence of ACL Avulsions in Schatzker Type IV Tibial Plateau Fractures: A 3D Quantitative Analysis Based on Mimics Software - Liu, Zihao; Wang, Shuai; Tian, Xiaochen; Peng, Aqin (The Journal of Knee Surgery, 2022)
Introduction Tibial plateau fractures are often accompanied with ligamental and meniscal injuries. Among which, the combined existence of Schatzker type IV fracture with anterior cruciate ligament (ACL) avulsion has been reported rarely. The purpose of this study was to determine the injury mechanism of Schatzker type IV fracture with ACL avulsion based on Mimics software.Methods Ninety-nine Schatzker type IV tibial plateau fractures were retrospectively analyzed by quantitative three-dimensional measurements. ACL avulsions were diagnosed through the data of computed tomography and magnetic resonance imaging. We simulated the knee posture when an injury occurred and defined different injury patterns. The chi-square test was used for determining the main mechanism which causes Schatzker type IV fractures associated with ACL avulsions.Results There were more ACL avulsions and more displaced ACL avulsions associated with the knee in flexion in the setting of Schatzker type IV fracture (p < 0.05). More ACL avulsions were found in the injury pattern of flexion-valgus than the other injury patterns of the same level (p < 0.05). The rotation of the tibial showed no significant difference in producing ACL avulsion fractures.Conclusion This study found that a flexed knee at the occurrence of a Schatzker type IV tibial plateau fracture is a high-risk factor for causing associated ACL avulsion and producing more displaced avulsions. Flexion-valgus pattern was the main cause of Schatzker type IV fractures associated with ACL avulsions. The findings will help orthopedists understand the injury mechanism and enhance their awareness of such injuries to avoid unfavorable prognosis.
Keywords: Schatzker type IV tibial plateau fractures; ACL avulsions; quantitative 3D measurements